Kecemasan Ditinjau dari Tingkat Perudungan pada Pelajar Sekolah SMA Negeri 1 Labuhan Deli - Romauli Br Silaban; Florencia Mauricee S; Caroline Valencia Cuandy; Geofanny Hardiansyah Simorangkir; Winida Marpaung; Petra Johanna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine and evaluate the relationship between bullying and students’s anxiety levels. The sample of this study consisted of 220 students from SMA Negeri 1 Labuhan Deli using non-proportional stratified random sampling technique. One of the scales used to obtain data on relationship between bullying and student anxiety levels is a Likert scale. This study contained 14 items on the anxiety scale and 30 items on the bullying scale. Based on the results of the study there is a positive correlation between Bullying Actions and Anxiety Level in SMA Negeri 1 Labuhan Deli students with a Person Correlation (r) value of 0.336 and p as much as 0.000 then p < 0.05, which means that the higher the Bullying Actions, the higher the Anxiety Level in SMA Negeri 1 Labuhan Deli students, and vice versa the lower the Bullying Actions the lower the Anxiety Level in SMA Negeri 1 Labuhan Deli students. Keywords: Bullying, Anxiety, Students of SMA Negeri 1 Labuhan Deli